2013
DOI: 10.3389/fpls.2013.00247
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional fructans and raffinose family oligosaccharides

Abstract: Fructans and raffinose family oligosaccharides (RFOs) are the two most important classes of water-soluble carbohydrates in plants. Recent progress is summarized on their metabolism (and regulation) and on their functions in plants and in food (prebiotics, antioxidants). Interest has shifted from the classic inulin-type fructans to more complex fructans. Similarly, alternative RFOs were discovered next to the classic RFOs. Considerable progress has been made in the understanding of structure–function relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(136 citation statements)
references
References 134 publications
3
116
1
Order By: Relevance
“…The trehalose of drought stressed leaves in our study may have been utilized as an osmolyte to provide the drought tolerance observed in the genotype SS8641. Myo-inositol acts as precursor of many metabolites especially raffinose that are involved in stress tolerance by providing membrane stability and antioxidative functions [56]. Decreased levels of raffinose of the drought stressed leaves can be accounted to the drought tolerance of the wheat plants (SS8641).…”
Section: Discussionmentioning
confidence: 99%
“…The trehalose of drought stressed leaves in our study may have been utilized as an osmolyte to provide the drought tolerance observed in the genotype SS8641. Myo-inositol acts as precursor of many metabolites especially raffinose that are involved in stress tolerance by providing membrane stability and antioxidative functions [56]. Decreased levels of raffinose of the drought stressed leaves can be accounted to the drought tolerance of the wheat plants (SS8641).…”
Section: Discussionmentioning
confidence: 99%
“…The trisaccharide raffinose can be found in many beans and vegetables (e.g., cabbage, brussels sprouts, broccoli, and asparagus), as well as cereals, where the free raffinose content in wheat bran is reported as Ͼ1% (45). Intriguingly, the accumulation of raffinose and stachyose, which is formed from raffinose by stachyose synthase, has been connected to biotic stress response in plants (46). Raffinose and stachyose are confirmed to have reactive oxygen species scavenging properties in plant cell membranes and thus contribute to cell membrane stability.…”
Section: Characterization Of a Novel Raffinose Oxidasementioning
confidence: 99%
“…Hydroxyl groups have been found to exert protective effects in response to dehydration stress in developing seed embryos of many crop plant species (Peterbauer and Richter 2001;Obendorf and Górecki 2012). The protective role of RFOs and fructans against abiotic stresses was last reviewed by ElSayed et al (2014) and Van den Ende (2013). However, the predominant objects in studies concerning the role of soluble carbohydrates in abiotic stress tolerance of vegetative tissues are model plants (Arabidopsis thaliana, Thellungiella halophyla) and crops naturally growing in moderate climate conditions.…”
Section: Introductionmentioning
confidence: 99%